Effect Of Balance Exercise and Tandem Stance Interventions to Improve Balance in the Elderly - Renni Hidayati Zein; Ayu Permata (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Elderly people are identified with various declining health conditions, especially physical health conditions. The health conditions of the elderly decline along with increasing age, which will affect the quality of life of the elderly. The worsening health condition of the elderly is contrary to the elderly's desire to remain healthy, independent, and able to carry out activities. Balance disorders are something that often occurs in the elderly. Balance is the basis of functional human movement for both children and the elderly. Weakened lower extremity muscle strength in the elderly can cause slow movement, short steps, feet not being able to move firmly enough and being more easily swayed so that balance becomes disturbed. Methods: This research is a pre-experimental research with a one-group pre-test & post-test design. The sample population is elderly people with balance disorders in Pekanbaru nursing homes. Collecting patient data using the Berg Balance Scale (BBS) pre-test and post-test. During the research period, the total sample was 22 respondents the sampling technique used was the cluster sampling technique, namely the selection of samples referring to groups with certain predetermined characteristics, namely those who met the inclusion criteria. Result: The results of the study showed an increase in balance before & after the intervention showing a significant change from the p value = 0.000 with a confidence level of 95%. Based on the Paired Sample T Test with a value of p = 0.000 < (0.05), it shows that there is an increase in balance in the elderly. Conclusion: It was concluded that the increase in balance before & after giving balance exercise and tandem stance showed an increase in balance in the elderly after being given with a frequency of 3 times a week for 1 month.